Intelligent Home Automation System Using Android Application - Gulhane, M; Ramnani, H; Kukde, S (International Journal of Computer Sciences and Engineering, 2025)
The proposed system that we introduced focuses on increasing the efficiency. While the cost of living is going up, there is a growing focus to involve technology to lower those prices. With this thought the project based on home automation allows the user to increase efficiency and maintain a house that is smart enough to reduce the electricity consumption while providing more automation. A home Automation System will sense its surrounding and take advantage to enhance the efficiency even if no one is present at home. With a house having home automation system, one can ensure that our house is at its best in power consumption and results in enhanced energy efficiency. With this upgrade of Automation technology, Quality of human life is increased significantly. In this world of technology there is a significant increase in the field of automation as it is making our life luxurious. With the rapid increase in the number of users of internet over the past decade has made Internet a part of once day-to-day life, and Internet of Things is the latest technology which is helping us in connecting devices or appliances through internet. Internet of things is a growing network of everyday from industries to Home Appliances that can execute the tasks the one want to perform while he/she is busy with other activities. Home Automation system using Internet of Things is a system that uses computers or mobile devices to control basic home appliances automatically through internet from anywhere around the world, an Home Automation System is sometimes called a smart home. It is meant to save the electric power and Time. The home automation system differs from other system by allowing the user to operate the system from anywhere around the world and also provides the feature of day and night mode which can control the appliances specifically light by sensing the intensity of the room.